Trends in Online Learning Research During the Covid-19 Pandemic in Higher Education: Bibliometric Studies - Apandi Apandi; Simon Sumanjoyo Hutagalung; Intan Fitri Meutia; Eko Budi Sulistio (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2023)
In order to break the chain of the Covid-19 virus, the government recommends schools lockdown and implementing online learning. The research problem formulation is as follows: (1). How is the trend of online learning studies during the covid-19 pandemic at universities in Indonesia? (2). What topics have developed in studying online learning during the COVID-19 pandemic at universities in Indonesia? The research was carried out as a literature review using bibliometric analysis of several sources of scientific publication data. The data in this study were obtained through literature collection techniques and their references which were obtained directly from the Scopus and Google Scholar databases. The data was extracted using the Publish or Perish tool and then analyzed with the VosViewer tool. From the analysis that has been done, it can be concluded that the distribution of authors who study online learning topics during the pandemic has not yet appeared to form a polarization of authorship networks that explore these topics in depth. Meanwhile, the trends that have formed in online learning during the pandemic seem to condense into several topics.